Prevalence of sarcopenia and its components in community-dwelling outpatient older adults and their relation with functionality - TUFAN ÇİNÇİN, ASLI (TAYLOR & FRANCIS LTD, 2020)
Aim Sarcopenia is recognized with its adverse functional outcomes. We aimed to report the prevalence of European Working Group on Sarcopenia in Older People (EWGSOP) defined sarcopenia and its individual components in community dwelling outpatient older adults and study the correlations of EWGSOP defined sarcopenia, muscle mass, muscle strength, and physical performance with functional status. Material and methods The subjects were prospectively recruited from the geriatrics outpatient clinics of our university hospital. Body composition was assessed with bioimpedance analysis. Muscle strength was assessed by measurement of hand grip strength with hydraulic hand dynamometer, physical performance was assessed by 4 meter usual gait speed (UGS). Impaired muscle function was defined as presence of low muscle strength and or slow gait speed. As a measure of functionality, modified version of Katz activities of daily living (ADL) and Lawton instrumental activities of daily living (IADL) were assessed. Results A total of 242 community dwelling outpatients with mean age of 79.4 +/- 5.7 years were enrolled. 31.8% were male. Prevalence of low muscle mass was 2.1% and impaired muscle function was 71.1%. Prevalence of EWGSOP defined sarcopenia was 0.8% (1.3% in men and 0.6% in women). Most correlated parameter with ADL and IADL was the usual gait speed (r = 0.49, r = 0.63; p < .001, respectively). Grip strength was also correlated with ADL and IADL (r = 0.28, r = 0.35; p < .001). However, the skeletal muscle mass index (SMMI) was not correlated with ADL, IADL (p = .22, p = .22, respectively). In regression analysis, both ADL score and IADL scores were most related to UGS (beta = 0.5 and 0.6, p < .001), age (beta = -0.25 and -0.2, p < .001) and then sarcopenia (beta = 0.1 and 0.1, p < .05) but was not related to hand grip strength or SMMI. Conclusions The prevalence of sarcopenia was low as 0.8% albeit the presence of impaired muscle function in more than 2/3 of the cases. We have found that EWGSOP defined sarcopenia had association with ADL and IADL. The gait speed component of sarcopenia had the strongest associations with functional measures but SMMI component did not have any relation. We suggest that although low muscle mass may be a parameter related to worse functionality, it should not be regarded prerequisite for presence of sarcopenia analogous to low bone mineral density for osteoporosis.
Keywords: EWGSOP; functionality; low muscle mass; muscle strength; sarcopenia; EUROPEAN CONSENSUS; NUTRITIONAL-STATUS; NURSING-HOME; MUSCLE MASS; OSTEOPOROSIS; ASSOCIATION; PEOPLE; DEFINITION; AGE; CONSEQUENCES